2004
DOI: 10.1116/1.1641049
|View full text |Cite
|
Sign up to set email alerts
|

Plasma characteristics in pulsed direct current reactive magnetron sputtering of aluminum nitride thin films

Abstract: Plasma diagnostics is important to identify plasma parameters and generate reproducible plasma in magnetron sputtering. Langmuir probes have been used to measure local plasma parameters such as electron temperature (Te), charge densities (ne and ni), and plasma potential (Vp). Pulsed direct current (dc) power in the midfrequency range (50–250 kHz) has been used in growing insulating films without charging accumulations at target. Recent investigations showed increased energetic particle bombardment of the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…Unlike conventional DC sputtering, many recent works on plasma diagnostics of pulsed DC magnetron sputtering has revealed that pulsing the magnetrons may modify many intrinsic plasma parameters [20][21][22] . Especially, with the increase of pulse frequency, the electron stochastic heating generated by fast switch of the target voltage between positive and negative will leads to a significant elevation in the electron temperature, electron density, ion energy and ion flux etc [24] .…”
Section: Characterization Of Microstructurementioning
confidence: 99%
See 4 more Smart Citations
“…Unlike conventional DC sputtering, many recent works on plasma diagnostics of pulsed DC magnetron sputtering has revealed that pulsing the magnetrons may modify many intrinsic plasma parameters [20][21][22] . Especially, with the increase of pulse frequency, the electron stochastic heating generated by fast switch of the target voltage between positive and negative will leads to a significant elevation in the electron temperature, electron density, ion energy and ion flux etc [24] .…”
Section: Characterization Of Microstructurementioning
confidence: 99%
“…Unlike conventional DC sputtering, many recent works on plasma diagnostics of pulsed DC magnetron sputtering has revealed that pulsing the magnetrons may modify many intrinsic plasma parameters [20][21][22] . Especially, with the increase of pulse frequency, the electron stochastic heating generated by fast switch of the target voltage between positive and negative will leads to a significant elevation in the electron temperature, electron density, ion energy and ion flux etc [24] . And on the other hand, higher pulse frequency means shorter pulse cycle, the transition period between the negative period and positive period will become a larger part in the pulse cycle, the power density in each pulse cycle and the high voltage overshoots at the beginning of the positive voltage period will be increased evidently.…”
Section: Characterization Of Microstructurementioning
confidence: 99%
See 3 more Smart Citations